Stakeholder Management Strategies in Enhancing the Effectiveness of Strategic Management in Schools - Mhd Novedy Husaini; Muhammad Syaifuddin (Journal of Practice Learning and Educational Development, 2026)
This research discusses how to manage stakeholders to improve the effectiveness of strategic management in schools by examining various available resources. From the analysis conducted, it was found that strategic management can function well if the school can manage stakeholders in an organized manner thru steps such as recognizing, mapping, communicating, engaging, building partnerships, and integrating them at all stages of the strategy. Involving stakeholders, both internal and external, helps create cooperation, increase resource support, and ensure accountability in decision-making. Additionally, improving capabilities and building a culture of cooperation has proven to continuously support the implementation of school strategies. This research emphasizes that strengthening relationships between stakeholders is crucial for achieving the best quality of education.